8 - Where is my Daddy? An Exploration of the Impact of Absentee Fathers on the Lives of Young People in Botswana - Thupayagale-Tshweneagae, Gloria; Mgutshini, Tennyson; Nkosi, Zethu Zerish (Africa Development, 2021)
A substantial body of research has consistently concluded that children growing up with absentee fathers are at an increased risk of maladjustment. This paper argues that co-parenting can have both direct and indirect or mediated effects on children. Co-parenting has an added benefit of modelling dyadic skills that include proving mutual emotional support, influence, and amicable resolution of disputes. Through qualitative data obtained in 2009 from 45 final year students at the University of Botswana, the authors conclude that African personhood is a larger-than-self conception, which also includes more than the physical being and shows that young people raised in father-absent families view their personhood as inferior, less guarded, and incomplete, relative to that of their counterparts who were born and raised in married-couple families. Living a full quality life eludes youth who were raised by mothers only, affirming the importance of fathers in the personhood of any individual.